If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 29 = q + -51 Reorder the terms: 29 = -51 + q Solving 29 = -51 + q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-1q' to each side of the equation. 29 + -1q = -51 + q + -1q Combine like terms: q + -1q = 0 29 + -1q = -51 + 0 29 + -1q = -51 Add '-29' to each side of the equation. 29 + -29 + -1q = -51 + -29 Combine like terms: 29 + -29 = 0 0 + -1q = -51 + -29 -1q = -51 + -29 Combine like terms: -51 + -29 = -80 -1q = -80 Divide each side by '-1'. q = 80 Simplifying q = 80
| 3a+5b=15 | | 8k+5k-10k= | | 56-d=27 | | 2+2u+7=42 | | w-10=58 | | 6=k-15 | | 4=m-63 | | 7x-3=x+7 | | 12-(3x-6)-5(7-x)= | | 39-w=2 | | y-65=9 | | (4t+9)-(-2+7)=0 | | A=p+pnr | | p-10=25 | | 8=n-65 | | 52q=32 | | b^4-ab^3+b^2c=0 | | 7*cos^2*x-cos*x-8=0 | | 71=-9n+8 | | 3*cos*2*x-5*cos*x-1=0 | | -3(y-2)=-5y+18 | | 7w-9=5(w+1) | | 7(y+6)-2y=2 | | 22-2x=14 | | .5x-2.4=.6 | | -4v+8(v-2)=-4 | | -3(4t-3)+5t=6t-5 | | 48+x(9+3)=288 | | 7u+5=5 | | -4v+8(v+2)=-4 | | 8g-7=-39 | | 3y+2f-f+1-3y+7=32 |